Personality characteristics, perception of pain and the attainment of self-care in patients with spinal fusion - Van der Merwe, Chanette (University of the Free State, 2017)
Background Self-care activities are often most affected after a spinal fusion and are priority goals of the individualised treatment approach. Many patients undergo spinal fusions with similar levels and instrumentation. Despite procedural similarities, some patients return to participation within self-care activities effortlessly, whilst others display delayed independence. Literature suggests that personality traits and patients` perceived experience of pain is two contributing factors in rehabilitation. The aim of this study was to investigate the associations between these factors. Methods A descriptive cross-sectional study design was used. The study population included 61 patients who underwent a spinal fusion amid October 2015 and June 2016. Data was gathered pre-operatively and post-operatively. Selfcompiled - and standardised questionnaires were used to measure pain, personality and self-care activities. Results Perfectionism (57.4%), tension (44.3%) and apprehension (44.3%) were high-indicated primary factors. Low emotional stability and seriousness were found in majority (73.8%) of the participants. Study participants (49.2%) who had high functional impairments due to pain displayed high levels of anxiety. Low levels of functional impairments were related to high levels of independence, tough-mindedness and self-control. Caring for toe nails, drying hair and engaging in sexual intercourse were the most affected self-care areas pre- and post-operatively. 68.9% of participants attained both self-care goals. Conclusion Participants with high anxiety and low independence, tough-mindedness and self-control, experienced more pain. Higher levels of pain are associated with decreased goal attainment. However, despite a higher pain perception, the presence of certain personality characteristics namely: low extraversion, high independence and self-control leads to higher goal attainment. Results confirm that personality characteristics influence pain perception and the attainment of self-care goals.
Keywords: Spinal fusion; Self-care, Health; Patients -- Rehabilitation; Pain -- Management; Dissertation (M. Occupational Therapy (Occupational Therapy))--University of the Free State, 2017